ANALISIS POLA TABUHAN BERUAS PADA MUSIK IRINGAN TARI JEPIN TALI BINTANG DI DESA KALIMAS KECAMATAN SUNGAI KAKAP KABUPATEN KUBU RAYA - Saprani, Saprani; Silaban, Chiristianly Yery (TACET Jurnal Pendidikan dan Kajian Seni, 2024)
Marching Band Bahana Kirana is one of the extracurricular activities that is very popular at Darussalam Sengkubang Islamic Boarding School. In addition, the achievements that have been obtained by Bahana Kirana Darussalam Sengkubang have also reached the West Kalimantan Province level in the highest percussion category. Therefore, the purpose of this research is to find out the basic learning of snare drums in basic double strokes in the extracurricular activities of the Marching Band Bahana Kirana. The method used is qualitative research with purposive sampling model data sources on the Head of Darussalam Sengkubang Islamic Boarding School, marching band coach, and snare drum players. Data collection was used with interview, observation, and documentation techniques. Data analysis uses reduction, presentation, and conclusion drawing and data validity techniques used by Sugiyono's extended observation and data triangulation model. The results revealed that the double stroke technique is a basic pattern commonly played and trained by the Bahana Kirana Marching Band. In addition, warming up is also important before doing a basic double stroke, in this case warming up is done in physical form and percussion instruments (snare drum). The important point of this research is that although the double stroke is a basic stroke, at least with the results of regular training and sufficient physical and instrumental warm-ups, it can produce optimal and maximum learning objectives.